Identification of novel RNA isoforms of LMNA. (3rd September 2017) - DeBoy, Emily; Puttaraju, Madaiah; Jailwala, Parthav; Kasoji, Manjula; Cam, Maggie; Misteli, Tom
ABSTRACT: The nuclear lamina is a proteinaceous meshwork situated underneath the inner nuclear membrane and is composed of nuclear lamin proteins, which are type-V intermediate filaments. The LMNA gene gives rise to lamin A and lamin C through alternative splicing. Mutations in LMNA cause multiple diseases known as laminopathies, including Hutchinson-Gilford Progeria Syndrome (HGPS), a premature aging disorder caused by a point mutation that activates a cryptic 5′ splice site in exon 11, resulting in a 150 bp deletion in the LMNA mRNA and the production of the dominant lamin A isoform progerin. During RNA sequencing analysis of wild type and HGPS patient skin fibroblasts, we discovered two novel LMNA isoforms. LMNAΔ447 and LMNAΔ297 use an alternative 3′ splice acceptor site in the 3′ untranslated region, and either the HGPS cryptic 5′ splice site in exon 11 or the wild type 5′ splice site. Both isoforms are present at low levels in HGPS patient and wild type cells in multiple cell types. We validate and quantify the expression levels of these novel isoforms in HGPS and wild type fibroblasts. Overexpression of either LMNAΔ447 or LMNAΔ297 is not sufficient to induce the typical HGPS cellular disease phenotypes and no significant difference in the two isoforms were found between young and old fibroblasts. These results identify and characterize two novel RNA isoforms of LMNA produced through alternative splicing.